The Role of Reward and Punishment Strategies in Enhancing Student Learning Motivation: A Pedagogical Perspective - Wahidiyah; Muhammad Munif (EDUCARE: Jurnal Ilmu Pendidikan, 2024)
This study aims to explore how reward and punishment strategies influence student learning motivation within the context of an Islamic boarding school. The research seeks to understand the pedagogical impact of these strategies in promoting academic engagement and character formation. Utilizing a qualitative case study method, data were collected through in-depth interviews with school leaders, teachers, and students, participant observation, and document analysis. The findings reveal that verbal praise and symbolic non-material rewards significantly enhance students' intrinsic motivation, foster greater enthusiasm for learning, and lead to improved academic performance. Meanwhile, religious-based punishments such as reading istighfar, reciting Surah Yasin, and public apologies help instill moral awareness and personal responsibility in a constructive manner. These dual strategies not only promote discipline and self-regulation but also nurture a spiritually supportive educational atmosphere. The implementation of both reward and punishment proves effective in creating a balanced and motivating learning environment, aligning with Islamic pedagogical values. The study contributes to the growing literature on holistic educational practices by offering insights into motivational dynamics in pesantren-based settings. It suggests that integrating intrinsic motivational strategies with spiritually grounded disciplinary methods can support both academic excellence and ethical development. As such, educators are encouraged to apply these approaches thoughtfully to maximize student potential within culturally and religiously contextualized learning environments.